Leadership Management of the Principal in Improving the Quality of Learning at SD Negeri 17 Bukitraya - Rosnaini; Azhar; Yuanita, Putri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
The leadership factor of school principals and teachers is the most dominant input component in influencing the quality of learning in an educational institution. This research aims to examine further the leadership management of school principals in improving the quality of learning at SD Negeri 17 Bukitraya. This research uses a qualitative approach with descriptive methods. Descriptive qualitative research is a research method that describes conditions or phenomena that exist in the field. Data collection techniques are documentation, observation, and interviews. The research subjects were the principal, head of curriculum, teachers, ADM staff, and student representatives at SD Negeri 17 Bukitraya. The research results show that 1) the plan proposed by the principal to improve the quality of learning at SD Negeri 17 Bukitraya has been effective. School principals have adopted various strategies to improve learning. 2) The organisation carried out by the school principal to improve the quality of learning is by distributing tasks to each school apparatus to carry out the progress of certain activities to completion. 3) The implementation of the principal's leadership management in improving the quality of learning at SD Negeri 17 Bukitraya has gone well. What the principal takes to improve quality is improving the quality of teacher teaching, or what is called increasing teacher professionalism. 4) Supervision of the implementation of the principal's leadership management in improving the quality of learning carried out at SD Negeri 17 Bukitraya can take the form of supervision of the principal.